Proto Street Art in Ljubljana in the 1980s and 1990s: The Case of Mizzart - Konda, Helena (SAUC - Street Art and Urban Creativity (repository), 2024)
Mizzart, a collective of students from different artistic fields, created large-scale paintings in the urban landscape in Ljubljana in the 1980s and 1990s. Their independent artistic practices in public space in the 1980s and 1990s could be described as ‘proto-street art’ – a new avenue of contemporary research in graffiti and street art studies. Based on a brief historical introduction of genealogical connections between street art and graffiti, upgraded with Rafael Schacter's classification of 'street art' as a defined artistic period, the article identifies the main characteristics of ‘proto-street art’, which are: the time of occurrence, agents, spontaneity/sovereignty, iconography, site specificity, unprofitability and interaction with public. Mizzart’s ephemeral cultural heritage is analysed by the proposed seven key formal elements of ‘proto-street art’.